Voltaic Cell Practical Guide Application Based on Mobile-Augmented Reality to Improve Student's Understanding Concepts - Aiza Alya; Achmad Lutfi; Kusumawati Dwiningsih (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the practicality, feasibility, and effectiveness of learning media as an augmented reality-based practicum guide application for students' conceptual understanding of voltaic cells. The application development used the Thiagarajan development method with the 4-D model (Define, Design, Develop, Disseminate), but it was sufficiently developed to be 3-D. A limited trial with seventeen Al-Falah Senior High School students was conducted in August 2021 on students who had been given voltaic cell material. Pretest-posttest sheets, validation-review sheets, and student response questionnaires were used as research instruments. The data analysis technique used quantitative description. Pretest and posttest results were analyzed based on normality, paired sample test, and N-gain. The results of this study indicated that the developed application could improve students' understanding of concepts. The application validation results obtained a content validation score of 94%, a construct validation score of 86%, a presentation-related validation score of 96%, and a language-related validation score of 90%, indicating that it was very valid. The application was practical because the average percentage of responses was 92%. Based on the t-test with a significance value of 5% that yielded the Sig value, the application was reported to be very effective. 0.00 0.05 (2-tailed) and an N-gain analysis score of 0.83 > 0.7.